Gender Identity in Early Childhood - Cervantes, J C (KnE Life Sciences, 2018)
Background. Some authors indicate that the origin of gender identity in children is between two and three years old. This research report presents evidence against this affirmation based on Cultural–historical Psychology about the acquisition of consciousness through language as a process that begins from early childhood and ends in adolescence. Objective. (1) Characterize concepts about gender identity that have children in early childhood. (2) To compare differences and similarities of the concept of gender identity in children of different ages. Design. The procedure used was the classifying pictures method adapted for this study. We evaluated 32 children from one to five years old about the acquisition of gender identity through a qualitative analysis of data. Results. It was found that children of two and three years old group images by gender stereotypes, while those of four and five are incorporating other criteria such as shape and color. Conclusion. This happens for two reasons: first, the incorporation of the gender culture is a complex process and second, the school promotes a classification system that allows to order the world based on criteria other than gender. Keywords: concepts, gender identity, early childhood, cultural–historical psychology, Mexico